2014
DOI: 10.3762/bjoc.10.193
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic bis(ureas) as ligands for anion complexation

Abstract: SummaryTwo macrocyclic bis(ureas) 1 and 2, both based on diphenylurea, have been synthesized. Compound 1 represents the smaller ring with two ethynylene groups as linkers and 2 the larger ring with two butadiynylene groups. On thermal treatment to 130 °C molecule 1 splits up into two dihydroindoloquinolinone (3) molecules. Both compounds 1 and 2 form adducts with polar molecules such as dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) and act as complexing agents towards a series of anions (Cl−, Br−, I−, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Urea groups have been especially effective incorporated into anion hosts due to the mini-pincer grips provided by proximal hydrogen bond donor NH groups. As a result, acyclic urea hosts (chelates) are prevalent. With the exception of bis-urea macrocycles, however, macrocyclic hosts containing only urea groups have been scarce. Expanding on earlier m -xylyl bis-urea chelates, , Reinhoudt and co-workers synthesized both acyclic chelates and macrocyclic tetraureas, and compared their anion binding effectiveness . They found that the macrocycles were selective for H 2 PO 4 – over other anions examined, with minimal binding observed for HSO 4 – in DMSO- d 6 .…”
mentioning
confidence: 99%
“…Urea groups have been especially effective incorporated into anion hosts due to the mini-pincer grips provided by proximal hydrogen bond donor NH groups. As a result, acyclic urea hosts (chelates) are prevalent. With the exception of bis-urea macrocycles, however, macrocyclic hosts containing only urea groups have been scarce. Expanding on earlier m -xylyl bis-urea chelates, , Reinhoudt and co-workers synthesized both acyclic chelates and macrocyclic tetraureas, and compared their anion binding effectiveness . They found that the macrocycles were selective for H 2 PO 4 – over other anions examined, with minimal binding observed for HSO 4 – in DMSO- d 6 .…”
mentioning
confidence: 99%